The possibilty of operating Burkina cotton in spening factories and the impact on the yarn produced - Hussein Ali Meabed (Journal of Architecture, Art & Humanistic Science, 2019)
Summary Study aims the possibility of operating Burkina cotton in spinning factories and the impact on the yarn produced which suitable with the wither circumstances, Maximize the value added of final products and identify quality range of the yarns to fabrics.• Previous studies:- Egyptian cotton and International famous - Prediction of the single yarn strength.- Effect of Spacer on yarn quality produced.Laboratory experimental testsThe researcher has produced three different counts, 16/1 Ne, 20/1 Ne, 30/1 Ne from Burkina. All tests have done at Golden Yarn Mil in Beni-Suef zoon and analysis for measuring strength, elongation, regularity, thin place, thick place and neps.Research Results:They include the results of the tests performed on the yarns with graphic relations graphs.1- The study proved that the spacer used in spinning M/C for producing count 16/1 Ne is the purple spacer where it gave best strength, higher regularity, lower thin place and lower thick place and neps. So it is the best spacer of all that used in experiments.2- The study proved that the spacer used in spinning M/C for producing count 20/1 Ne is the Red spacer where it gave best strength, higher regularity, lower thin place and lower thick place and neps. So it is the best spacer of all that used in experiments.3- The study proved that the spacer used in spinning M/C for producing count 30/1 Ne is the cream spacer where it gave best strength, higher regularity, lower thin place and lower thick place and neps. So it is the best spacer of all that used in experiments.